2018
DOI: 10.3329/bmrcb.v43i1.35152
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori cagA gene Polymorphism in Patients with Gastroduodenal Diseases

Abstract: Helicobacter pylori is a genetically diverse bacterial pathogen and its CagA gene is a major virulence factor that plays an important role in gastroduodenal pathologies. The biological function of cagA depends on tyrosine phosphorylation within the EPIYA (Glutamate-Proline-Isoleucine-TyrosineAlanine) motifs at the C-terminal region of the protein. This region may undergo polymorphism to give different types of EPIYA motifs. EPIYA motif diversity may provide a useful tool for prediction of H. pylori pathogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…The male to female ratio was 2:1 in the present study. This study correlates with that of Chowdhury et al 15 .…”
Section: Resultssupporting
confidence: 93%
“…The male to female ratio was 2:1 in the present study. This study correlates with that of Chowdhury et al 15 .…”
Section: Resultssupporting
confidence: 93%
“…Jose et al (28) showed that the blastogenic response of T lymphocytes was altered in children with moderate malnutrition and in children recently recovered from PEM. Chowdhury et al (29) also showed that children with PEM had defects in blastogenesis of lymphocytes after stimulation with phytohemagglutinin. McMurray et al (31) evaluated 43 Colombian children: 21 had kwashiorkor, 11 had marasmus‐kwashiorkor, and 11 had marasmus.…”
Section: Discussionmentioning
confidence: 99%